A 'Reuse Projection Framework' Based on Othello's Citadel and Cultural Tourism. (2nd July 2020) - Joudifar, Farnaz; Olgaç Türker, Özlem
ABSTRACT: Conserving and sustaining heritage buildings for future generations is a challenging issue. Hence, this study seeks an alternative means of identifying appropriate new functions for heritage buildings with rich historical layers, through a developed 'Reuse Projection Framework'. The framework has been developed through a variety of research methodologies to determine appropriate functions for architectural monuments in general and Othello's Citadel in the Walled-City of Famagusta in particular. The first step of the Framework covers analytical and practical research based on a literature survey and in-situ observation. Next, it explores architectural and historical features to identify those architectural layers and alterations over time. Lastly, it examines the heritage values of the monument to assess its significance. In light of the first step, possible options for re-use within sustainable tourism scenarios are defined. In the second step of the proposed framework stakeholder opinions of new functions, are investigated through quantitative methods based on a questionnaire survey. The survey was conducted with the local community and cultural tourists as potential end users of re-use functions, as well as heritage experts from governmental and non-governmental bodies. The comparative results obtained from different stakeholders are interpreted to make suggestions for appropriate functions for future.